Educational Development Index of Bihar Towards a Better Tomorrow - Singh, Chandra P.B. (JOURNAL OF INDIAN EDUCATION, 2018)
The study was designed to compute district-wise educational development index of Bihar. At the same time, an attempt was made to assess the trend of improvement in elementary education for the last few years. U-DISE data for the last two years (2014–15 and 2015–16) was analysed and compared with the baseline data. Bihar showed significant improvement on many parameters of elementary education. Despite the fact that Bihar is yet to achieve the desirable level but the progress is evident. Other than learning achievement, in terms of quality Bihar has shown her firm determination to change the gloomy picture of elementary education. The findings reflect a positive trend of upward movement. Right from access to teachers in school, Bihar has made progress in the light of RTE Act, 2009.